Analyzed polarized reflectance model of typical surface types over China based on the PARASOL measurements. (September 2016) - Xiang, Kun-Sheng; Cheng, Tian-Hai; Gu, Xing-Fa; Guo, Hong; Chen, Hao; Wang, Ying; Wei, Xi; Bao, Fang-Wen; Kong, Fan-Ping
Abstract: In this paper, the parameters of four types of polarization reflectance models (the Breon physical model, the Nadal–Breon semi-empirical model, the Maignan et al. single parameter model, and the Litvinov et al. model) were analyzed based on the PARASOL observation of three typical features in China three sites (forest, grassland, and desert). Subsequently, combined with the model analysis, the polarization reflectance characteristics of each typical feature were studied. The results reveal that 1) the imitative effect of the Litvinov et al. model about forest was the best, as the linear slope was greater than 0.9 and R 2 was better than 0.8; 2) the linear slope and R 2 of the Nadal–Breon model about all surfaces were higher than 0.8; 3) although fitting slope of the Maignan et al. model was bad under the forest (0.15<NDVI<0.3) background, the fitting effect was the best for desert and grassland. The results will provide a theoretical basis for the use of multi-angle polarization remote sensing data to detect the physical properties of the surface type and provide a priori knowledge for the quantitative inversion of surface atmospheric parameters. Highlights: Applicability of four polarization reflectance models over China was analyzed. Litvinov et al. model of the forest fitting effect was the best. Maignan et al. model of the grassland and desert fitting effect was the best. All the models have a better fitting effect on desert than other features.